Taxonomizing a truly morphologically cryptic complex of dwarf geckos from Madagascar: molecular evidence for new species-level lineages within the Lygodactylus tolampyae complex - Vences, Miguel; Multzsch, Malte; Zerbe, Milena; Gippner, Sven; Andreone, Franco; Crottini, Angelica; Glaw, Frank; Köhler, Jörn; Rakotomanga, Sandratra; Rasamison, Solohery; Raselimanana, Achille P. (Zootaxa, 2024)
The Lygodactylus tolampyae complex includes several deep genetic lineages of small diurnal geckos from the West and North West of Madagascar whose taxonomy is largely unsolved. We sequenced DNA fragments of one mitochondrial and four nuclear-encoded genes for up to 70 samples across the entire known range of these geckos. We find as many as 11 mitochondrial lineages differentiated by >4% pairwise distances in the 16S rRNA gene fragment, with >9% pairwise distance for the majority of lineage comparisons. Many of these lineages were concordantly differentiated in all of the nuclear-encoded genes without any haplotype sharing, despite the syntopic occurrence of some of them. We therefore hypothesize that the complex contains seven candidate species, but a comprehensive taxonomic resolution is complicated by various hindrances. These include incomplete sampling, with two lineages each known only from a single specimen, and one further lineage with no voucher specimens available for examination. Further hurdles are the probably lost holotype of L. tolampyae and its imprecise type locality, as well as the apparent lack of any morphological differentiation between the majority of the genetic lineages. Based on a survey of historical literature and the travel routes of the original collector, A. Grandidier, we conclude that the provenance of the holotype of L. tolampyae is likely in the wider Morondava area in the West and assign the sole candidate species from this area to this name. We then proceed to describe three species that represent separate genetic lineages for all markers studied: Lygodactylus morii sp. nov., a species common in Ankarafantsika National Park and several nearby sites in the North West; L. herilalai sp. nov., a species occurring in close syntopy with L. morii in Ankarafantsika without any signal of genetic admixture; and L. schwitzeri sp. nov. from Sahamalaza Peninsula in the North West. This leaves three more lineages without a name and with the need to gather additional samples, two from Namoroka National Park and one from other sites in the North West. We confirm the L. tolampyae complex to be an apparently rare example of truly cryptic reptile species in Madagascar, where even detailed morphological examination does not reveal morphological differences among lineages that are clearly evolutionarily independent and require recognition as distinct species due to their co-occurrence without admixture.